Death in southern Patagonian fjords: Copepod community structure and mortality in land- and marine-terminating glacier-fjord systems. (May 2019) - Giesecke, R.; Höfer, J.; Vallejos, T.; González, H.E.
Highlights: Marine terminating glacier fjord support high phytoplankton and zooplankton biomass. Copepod mortality is linked with high loads of inorganic suspended matter (ISM). Larger copepods tend to be more susceptible to high load ISM than small copepods. Copepod carcasses contribute to less than 3.5% of the exported carbon to the benthos. Abstract: Glacial retreat at high latitudes has increased significantly in recent decades associated with global warming. Along Chile's Patagonian fjords, this has promoted increases in freshwater discharge, vertical stratification, and the input of organic and inorganic particles to fjords. In addition, it has modified the water chemistry [i. e. nutrient stoichiometry] and its associated biota. This study evaluates the effect of deglaciation in high-latitude fjords (54°S) on copepod survival and how this might affect the export of particulate organic carbon to the benthos. We selected two contrasting fjord systems in terms of their geomorphology and the quality and quantity of freshwater contributions: (a) Pia Fjord, with marine-terminating glaciers, and (b) Yendegaia Fjord, with land-terminating-glaciers. Both are located along the Beagle Channel (54°S), southern Chilean Patagonia. These two fjords differed significantly in phytoplankton and copepod biomass. Whereas Pia Fjord showed high chlorophyll-a concentration (7 mg Chl-a m −3 ) and copepod abundance (970 ind. m −3 ), in Yendegaia Fjord, the biomass was very low for both autotrophs (<0.3 Chl-a m −3 ) and copepods (470 ind. m −3 ). Conversely, a greater proportion of copepod carcasses was recorded in Pia (22%) versus Yendegaia (18%), with small copepods (600–1000 µm prosome length) being less affected than large ones (>1000 µm). The presence of carcasses was better explained by the amount of suspended particulate inorganic matter in the water column than by salinity. The contribution of dead copepods to the vertical carbon flux was <3.5% of the total carbon exported down to 50 m depth, with contributions of 9.5 ± 9.9 mgC m −2  d −1 in Yendegaia and 10.8 ± 10.8 mgC m −2  d −1 in Pia. Our results suggest that heavy deglaciation processes in high-latitude fjords may reduce phytoplankton biomass, causing the copepod abundance to decrease and non-predatory mortality in filter-feeding copepods to decline.